Two-dimensional DOA estimation of coherent sources using two parallel uniform linear arrays - Heping Shi; Zhuo Li; Jihua Cao; Hua Chen (EURASIP Journal on Wireless Communications and Networking, 2017)
Abstract A novel two-dimensional (2-D) direction-of-arrival (DOA) estimation approach based on matrix reconstruction is proposed for coherent signals impinging on two parallel uniform linear arrays (ULAs). In the proposed algorithm, the coherency of incident signals is decorrelated through two equivalent covariance matrices, which are constructed by utilizing cross-correlation information of received data between the two parallel ULAs and the changing reference element. Then, the 2-D DOA estimation can be estimated by using eigenvalue decomposition (EVD) of the new constructed matrix. Compared with the previous works, the proposed algorithm can offer remarkably good estimation performance. In addition, the proposed algorithm can achieve automatic parameter pair-matching without additional computation. Simulation results demonstrate the effectiveness and efficiency of the proposed algorithm.